Assessing cerbera odollam matured and immature fruit extract for antimicrobial activity - Nurulfarahana Binti Harun (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
The problem of resistance among bacteria against available antibiotics or drug is involves a great challenge to the current world. The research should be further to overcome this problem without affecting the surrounding or the environment. The current study pertained to the susceptibility of Streptococcus pyogenes to various crude extracts of immature and matured Cerbera odollam fruits by disc diffusion method. The Minimum inhibition concentrations (MIC) were further evaluated against this bacteria to observe the lowest concentration of various crude extract that will inhibit the growth of the bacteria. This study indicated that the antibacterial activities are dependent on the type of the extract and the maturity of the C. odollam. Methanol extracts show the comparatively higher antibacterial activity against this bacteria than the ethanol extracts. Furthermore, Methanol extracts also evaluated as a higher percentage yield compared the ethanol extracts. While, matured C. odollam observed higher antibacterial activity better than the immature C. odollam. Minimum inhibition concentration (MIC) for matured methanol extracts data showed hopeful results as some of the extracts exhibited significant inhibitions of bacteria even at concentration as low as 4 ppm. Overall, C. odollam seems to have a significant antibacterial activity and to be very useful in the discovery and research of novel antibiotics.